Peran Penyuluh Pertanian Terhadap Peningkatan Produksi Usahatani Padi Sawah di Kelurahan Lalosabila Kecamatan Wawotobi Kabupaten Konawe - Astina Astina; Leni Saleh; Mursal Junus (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The purpose of this study was to analyze the role of extension workers in increasing the production of rice farming in Lalosabila Village, Wawotobi District, Konawe Regency, Southeast Sulawesi. Informants consisted of key informants and supporting informants. Key informants are the main source of information related to the problem being studied. The total number of respondents in this study was 16 people who would be used as samples. The role of agricultural extension workers in increasing the production of rice farming in Lalosabila Village, Wawotobi District, Konawe Regency can be described as follows: The role of extension workers as educators was obtained with an average score of 2.27 (moderate), The role of extension workers as organizers and dynamists obtained an average score of 2.40 (high), The role of extension workers as motivators obtained an average score of 2.81 (high), The role of extension workers as facilitators obtained an average score of 2.65 (high).